Conservative management of a dentigerous cyst associated with an impacted mandibular second premolar in mixed dentition: a case report - Pradeep Kumar Mohapatra; Namita Joshi (Tabriz University of Medical Sciences, 2009)
Dentigerous cysts, commonly encountered in the practice of dentistry, are benign odontogenic cysts associated with crowns of unerupted and/or impacted permanent teeth. They frequently occur during the second and third decades of life. Treatment modalities range from enucleation to marsupialization, which may be influenced by the age of the patient, severity of impaction, and root form of associated tooth/teeth. The purpose of this report is to describe the successful outcome of conservative surgical management of a large dentigerous cyst associated with an impacted mandibular second premolar in a young patient.